(untitled) (Research, Society and Development, 2022)
This study is a literature review which aims to discuss the impacts of sedentary behavior in schoolchildren lives, presenting possible solutions to reduce the problem and, consequently, contribute to positive public health. For this, we used works published from 2017 to 2021 available on the Scielo and Google Academic platforms. Therefore, it is established a parallel between sedentary lifestyle and obesity, contextualized by Covid-19, presenting the implications for the emergence of chronic diseases. Accordingly, the study aims to display possible attitudes capable of reducing levels of physical inactivity, emphasizing the importance of Physical Education in the school and out-of-school context, as it is evident that this is one of the ways to educate students to adopt healthy habits that will reflect in the positive behaviors of the future, being an important way to encourage the practice of physical activity, considering that obesity and the tendency to sedentary behavior is not only dominant in adults and elderly, but it is also a problem that affects the public of young students.